2005
DOI: 10.1242/jcs.02338
|View full text |Cite
|
Sign up to set email alerts
|

Complexin II facilitates exocytotic release in mast cells by enhancing Ca2+ sensitivity of the fusion process

Abstract: Recent studies have shown that soluble N-ethyl maleimide-sensitive factor attachment protein receptor (SNARE) proteins are involved in exocytotic release in mast cells as in neurotransmitter release. However, the roles of the proteins that regulate the structure and activity of SNARE proteins are poorly understood. Complexin is one such regulatory protein and is involved in neurotransmitter release, although ideas about its role are still controversial. In this study, we investigated the expression and role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
65
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 45 publications
(46 reference statements)
1
65
0
Order By: Relevance
“…On the other hand, we reported that knock-down of complexin II decreases exocytotic release in mast cells. 10) Complexin I binds to SNARE complex in nerve terminal and make it stable, 23) therefore it is reasonable that SNARE complex become unstable in mast cells when complexin II is knocked down. We think that synaptotagmin 2 fails to bind to unstable SNARE complex, resulting in decrease of Ca 2+ sensitivity and exocytotic release.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, we reported that knock-down of complexin II decreases exocytotic release in mast cells. 10) Complexin I binds to SNARE complex in nerve terminal and make it stable, 23) therefore it is reasonable that SNARE complex become unstable in mast cells when complexin II is knocked down. We think that synaptotagmin 2 fails to bind to unstable SNARE complex, resulting in decrease of Ca 2+ sensitivity and exocytotic release.…”
Section: Discussionmentioning
confidence: 99%
“…10) Complexin II also interacts with SNARE complexes containing SNAP-23, syntaxin-3, and VAMP-2 or -8 in mast cells. 20) We examined whether these SNARE proteins induce membrane fusion between liposomes.…”
Section: Fusion Degree Between Mast Cell Snare-containingmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon elevation of intracellular Ca 2ϩ , complexin 1 was proposed to be displaced from the SNARE complex by synaptotagmin 1, in turn allowing the final stages of neurotransmitter release to commence (7). More recent studies have shown that in addition to this clamping activity, complexin 1 also directly facilitates the final stages of exocytosis (9,10).…”
mentioning
confidence: 99%